2018
DOI: 10.4314/ejhs.v28i1.7
|View full text |Cite
|
Sign up to set email alerts
|

Sub-optimal breastfeeding and its associated factors in rural communities of Hula District, southern Ethiopia: a cross-sectional study

Abstract: BACKGROUND: Sub-optimal breast feeding contributed a significant number of infants' death. Although breast feeding is universal in Ethiopia, the practice is not optimal. Hence, this study assessed the prevalence of sub-optimal breast feeding practice and its associated factors in rural communities of Hula District, Southern Ethiopia. METHODS: A community based cross-sectional study was conducted among 634 women with infants aged 6 to 12 months. Multistage sampling technique was employed to select study subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
38
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 25 publications
9
38
3
Order By: Relevance
“…Mothers with primary and above school qualification seemed to perform better with respect to IFPs than illiterate mothers. This finding is in agreement with previous studies in Ethiopia and elsewhere [13,42,44,45,75]. This may be explained by educated mothers having better understanding of IYCF itself and/or had exposure to IYCF awareness raising campaigns (through their ability to read leaflets, posters and banners) that have been conducted for several years by the Ministry of Health and development partners in Ethiopia.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Mothers with primary and above school qualification seemed to perform better with respect to IFPs than illiterate mothers. This finding is in agreement with previous studies in Ethiopia and elsewhere [13,42,44,45,75]. This may be explained by educated mothers having better understanding of IYCF itself and/or had exposure to IYCF awareness raising campaigns (through their ability to read leaflets, posters and banners) that have been conducted for several years by the Ministry of Health and development partners in Ethiopia.…”
Section: Discussionsupporting
confidence: 91%
“…Systematic reviews in 2019 and 2015concluded that depressed women breastfed their child for shorter duration than nondepressed women [23,41]. Other previous studies also reported a negative association between maternal depression and early initiation of breastfeeding [42], complementary feeding initiation [43] and infants' dietary diversity [44,45].…”
Section: Discussionmentioning
confidence: 96%
“…Systematic reviews in 2019 and 2015concluded that depressed women breastfed their children for shorter duration than non-depressed women [30,31]. Other previous studies also reported a negative association of maternal depression with early initiation of breastfeeding [28], timey complementary feeding initiation [27] and infants' dietary diversity [34,35].…”
Section: Discussionmentioning
confidence: 96%
“…Among the psychosocial factors, prenatal and postnatal depression consistently predicted components of IFPs such as breastfeeding initiation [28,29], exclusive breastfeeding [30][31][32], breastfeeding duration [33] complementary feeding timely initiation [27] and dietary diversity [34,35]. Moreover, researchers reported that other psychosocial factors such as intimate partner violence and maternal social support are important predictors of IFPs.…”
mentioning
confidence: 99%
“…10 Recent reports suggests that, globally only 38% of infants aged 0-6 months were breastfed between periods of 2007-2014. 11 Global breastfeeding scorecard report indicates that 45% of children are put to breast within 1 hour of birth, 43% children are exclusively breastfed at 0-5 months and 46% children are continued to be breastfed till 2 years of age. 10 Recent National Family health Survey-4 of India reported the prevalence of early initiation of breastfeeding within 1 hour as 41.6% and exclusive breastfeeding up to 6 months as 54.9%.…”
mentioning
confidence: 99%